High-temperature-resistant special gas filtering aluminum oxide ceramic membrane and preparation method thereof
Through high-pressure hydrothermal method and microwave low-temperature sintering technology, nanozirconia wraps alumina ceramic particles, solving the problem of ceramic films prone to cracking in high-temperature environments, significantly improving temperature resistance and thermal shock resistance, expanding application range and market potential .
Patent Information
- Application Number
- CN202411246190.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-31
AI Technical Summary
The existing special gas filtered alumina ceramic membrane is prone to cracking in high temperature environments, has a high thermal expansion coefficient and poor thermal shock resistance, making it difficult to take into account both filtration accuracy and temperature resistance, which limits its application scope and market development.
The nanozirconia is uniformly wrapped around the surface and interior of alumina ceramic particles by high-pressure hydrothermal method. Combined with microwave low-temperature sintering technology, the reinforcement and toughening effect of nanozirconia is used to reduce the thermal expansion coefficient of alumina and form it through secondary high-temperature sintering. High temperature resistant special gas filtered alumina ceramic membrane.
It significantly improves the temperature resistance and thermal shock resistance of ceramic films, expands the temperature resistance range to 350℃, and maintains 10-15 times without cracking and falling off in the thermal shock resistance test of 350℃, solving the accuracy and resistance of traditional ceramic films. The problem of difficult to take into account both temperature performance.
Smart Images

Figure CN119215685A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic membrane preparation, and specifically relates to a high-temperature resistant special gas filtering alumina ceramic membrane and a preparation method thereof. Background Art
[0002] Specialty gas filtration ceramic membranes are key materials for the filtration and purification of electronic specialty gases, and play a vital role in the semiconductor manufacturing process. These ceramic membranes must have extremely high purity and cleanliness to ensure the quality and performance of electronic specialty gases, and thus the quality and reliability of semiconductor devices. In semiconductor manufacturing, the main function of electronic specialty gas filtration ceramic membranes is to remove particles, moisture and other potential contaminants from the gas. If these contaminants are not effectively removed, it may cause the performance of semiconductor devices to deteriorate, or even cause the entire production batch to be scrapped.
[0003] The mainstream special gas filtration ceramic membranes on the market are mainly made of alumina. However, alumina has a high thermal expansion coefficient, is not resistant to temperature shock, and has poor thermal shock resistance. Therefore, it is prone to severe cracking in high temperature or thermal shock scenarios and is generally only suitable for room temperature environments (such as Figure 1 As shown in the figure). For high temperature environments, materials with good thermal shock resistance are usually used, although the filtration accuracy may be poor. This limitation in material selection makes it difficult for special gas filtration ceramic membranes to strike a balance between filtration accuracy and temperature resistance, which seriously restricts the application scope and market development of special gas filtration alumina ceramic membranes. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a high temperature resistant special gas filtering alumina ceramic membrane and a preparation method thereof.
[0005] The technical solution of the present invention is as follows:
[0006] A high temperature resistant special gas filtering alumina ceramic membrane and a preparation method thereof, comprising the following steps:
[0007] (1) mixing an alumina ceramic powder having an average particle size of 100-800 nm with a nano zirconium oxide dispersion having a concentration of 5-10 wt %, and reacting the mixture under high pressure hydrothermal conditions of 10-16 MPa and 300-350° C. for 3-5 h, wherein the average particle size of the nano zirconium oxide in the nano zirconium oxide dispersion is 10-30 nm;
[0008] (2) drying the material obtained in step (1), and then sintering it once at 520-580° C. for 25-35 min using a microwave heating device to obtain zirconium oxide-coated alumina powder;
[0009] (3) ball-milling and mixing the zirconium oxide-coated alumina powder obtained in step (2), PVA with an average particle size of 0.8-1.2 μm, RO water, polysiloxane defoamer and methyl cellulose thickener;
[0010] (4) coating the material obtained in step (3) on a high temperature resistant gas filtration silicon carbide, cordierite or alumina support to obtain a wet blank;
[0011] (5) The wet blank obtained in step (4) is shade-dried at room temperature, then dried, and then sintered at 1350-1450° C. for 3-5 hours to obtain the high-temperature resistant special gas filtering alumina ceramic membrane.
[0012] In a preferred embodiment of the present invention, in the step (1), the purity of Al2O3 in the alumina ceramic powder is greater than 99.9%, and the purity of ZrO2 in the nano zirconium oxide is greater than 99.9%.
[0013] In a preferred embodiment of the present invention, the drying temperature in step (2) is 120° C. and the drying time is 4 hours.
[0014] In a preferred embodiment of the present invention, in step (3), the ratio of zirconium oxide-coated alumina powder, PVA, RO water, polysiloxane defoamer and methyl cellulose thickener is 20-25wt%: 2-2.5wt%: 70-77wt%: 0.01-0.03wt%: 0.99-2.48wt%.
[0015] Further preferably, in step (3), the average particle size of the PVA is 1 μm.
[0016] In a preferred embodiment of the present invention, in the step (4), the shade drying time is 4 hours.
[0017] In a preferred embodiment of the present invention, in the step (4), the drying temperature is 105° C. and the drying time is 2 h.
[0018] In a preferred embodiment of the present invention, in the step (1), the purity of Al2O3 in the alumina ceramic powder is greater than 99.9%, and the purity of ZrO2 in the nano zirconium oxide is greater than 99.9%; in the step (3), the ratio of zirconium oxide-coated alumina powder, PVA, RO water, polysilicone defoamer and methyl cellulose thickener is 20-25wt%: 2-2.5wt%: 70-77wt%: 0.01-0.03wt%: 0.99-2.48wt%.
[0019] Further preferably, in step (3), the average particle size of the PVA is 1 μm.
[0020] More preferably, in step (4), the shade drying time is 4 hours; the drying temperature is 105° C. and the drying time is 2 hours.
[0021] The beneficial effects of the present invention are:
[0022] 1. The present invention firstly adopts a high-pressure hydrothermal method to uniformly wrap nanoparticles on the surface of alumina ceramic particles and fill the crack defects inside the particles; then, by using microwave low-temperature rapid one-time sintering technology, through a uniform and rapid heating process, combined with the high wave absorption efficiency of nano zirconium oxide particles (this efficiency is better than that of large-particle α-alumina), the nano zirconium oxide particles are stably and rapidly bonded to the surface of alumina ceramic powder and the cracks inside the particles; this effectively avoids the defects and unevenness of the ceramic film support body that may be caused by the desorption, agglomeration and segregation of nanoparticles during subsequent ball milling, coating and sintering processes, and at the same time solves the problem of abnormal agglomeration and growth of nano grains caused by uneven temperature in traditional heating methods.
[0023] 2. The present invention only uses nano-zirconia as a sintering aid, and utilizes its reinforcing and toughening effect on alumina to reduce the thermal expansion coefficient of alumina ceramics, thereby significantly improving the temperature resistance and thermal shock resistance of the special gas filtration alumina ceramic membrane.
[0024] 3. The high-temperature resistant special gas filtration alumina ceramic membrane prepared by the present invention has achieved a qualitative leap in temperature resistance and thermal shock resistance, effectively solving the problem that the existing special gas filtration ceramic membrane is difficult to balance between precision and temperature resistance, which has seriously restricted the application scenarios and market development of special gas filtration alumina ceramic membranes. In other words, the present invention provides a strong technical guarantee for the large-scale application and promotion of special gas filtration ceramic membranes. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a surface electron microscope photograph of the special gas filtration ceramic membrane in the background technology of the present invention.
[0026] Figure 2 This is a surface electron microscope photograph of the high-temperature resistant special gas filtration alumina ceramic membrane prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0027] The technical solution of the present invention is further illustrated and described below through specific implementation modes in combination with the accompanying drawings.
[0028] Example 1
[0029] (1) Alumina ceramic powder (Al2O3 purity> 99.9%, average particle size 100 nm) was mixed with nano zirconium oxide dispersion (concentration of 5 wt%, ZrO2 purity> 99.9%, average particle size 20 nm), and reacted under high pressure (16 MPa) hydrothermal (350°C) conditions for 4 h;
[0030] (2) drying the material obtained in step (1) at 120° C. for 24 h, and then sintering the material at 520° C. for 30 min using a microwave heating device to obtain zirconium oxide-coated alumina powder;
[0031] (3) The zirconium oxide-coated alumina powder, PVA (average particle size of 1 μm), RO water and appropriate amounts of polysiloxane defoaming agent and methyl cellulose thickener obtained in step (2) are ball-milled for 4 hours using a ball mill, wherein the ratio of the zirconium oxide-coated alumina powder, PVA, RO water, polysiloxane defoaming agent and methyl cellulose thickener is 20wt%: 2wt%: 77wt%: 0.01%: 0.99wt%.
[0032] (4) coating the material obtained in step (3) on a high temperature resistant gas filtering silicon carbide support to obtain a wet blank.
[0033] (5) The wet blank obtained in step (4) is dried in the shade at room temperature for 4 hours, then slowly heated to 105° C. in an oven for drying for 2 hours, and then sintered at 1350° C. in a high-temperature sintering electric kiln for 4 hours to obtain the high-temperature resistant special gas filtration alumina ceramic membrane (surface such as Figure 2 As shown, since only nano-zirconia is used as a sintering aid, its strengthening and toughening effect on alumina reduces the thermal expansion coefficient of alumina ceramics and significantly improves the temperature resistance and thermal shock resistance of alumina ceramic membranes for special gas filtration).
[0034] The high temperature resistant special gas filtering alumina ceramic membrane can withstand temperatures up to 350°C (thermal shock resistance test: the filter membrane does not crack or fall off after being rapidly cooled from 350°C to room temperature for more than 10 times), and its 350°C thermal shock resistance test can reach 13 times. In comparison, the ceramic membrane made by simple mechanical mixing of the same raw materials has a temperature resistance of only 120°C (thermal shock resistance test: the filter membrane does not crack or fall off after being rapidly cooled from 120°C to room temperature for more than 10 times), and its 350°C thermal shock resistance test is only 0 times.
[0035] Example 2
[0036] (1) Alumina ceramic powder (Al2O3 purity> 99.9%, average particle size 800nm) and nano zirconium oxide dispersion (concentration of 10wt%, ZrO2 purity> 99.9%, average particle size 30nm) were mixed and reacted under high pressure (10MPa) hydrothermal (300℃) conditions for 4h;
[0037] (2) drying the material obtained in step (1) at 120° C. for 24 h, and then sintering the material at 580° C. for 30 min using a microwave heating device to obtain zirconium oxide-coated alumina powder;
[0038] (3) The zirconium oxide-coated alumina powder, PVA (average particle size of 1 μm), RO water and appropriate amounts of polysiloxane defoamer and methyl cellulose thickener obtained in step (2) are ball milled for 4 hours using a ball mill, wherein the ratio of the zirconium oxide-coated alumina powder, PVA, RO water, polysiloxane defoamer and methyl cellulose thickener is 25wt%: 2.5wt%: 70wt%: 0.02%: 2.48wt%.
[0039] (4) coating the material obtained in step (3) on a high temperature resistant gas filtering alumina support to obtain a wet blank.
[0040] (5) The wet blank obtained in step (4) is dried in the shade at room temperature for 4 hours, then slowly heated to 105°C in an oven and dried for 2 hours, and then subjected to secondary high-temperature sintering in a high-temperature sintering electric kiln at 1450°C for 4 hours to obtain the high-temperature resistant special gas filtration alumina ceramic membrane (the surface morphology is basically the same as that in Example 1).
[0041] The performance of the high temperature resistant special gas filtering alumina ceramic membrane is as follows: temperature resistance up to 350℃, thermal shock resistance (thermal shock resistance test: the filter membrane does not crack or fall off after being rapidly cooled from 350℃ to room temperature for more than 10 times), and its 350℃ thermal shock resistance test can reach 15 times. In comparison, the ceramic membrane made by simple mechanical mixing of the same raw materials has a temperature resistance of only 150℃ (thermal shock resistance test: the filter membrane does not crack or fall off after being rapidly cooled from 150℃ to room temperature for more than 10 times), and its 350℃ thermal shock resistance test is only 0 times.
[0042] Example 3
[0043] (1) Alumina ceramic powder (Al2O3 purity> 99.9%, average particle size 300nm) and nano zirconium oxide dispersion (concentration 8wt%, ZrO2 purity> 99.9%, average particle size 20nm) were mixed and reacted under high pressure (10MPa) hydrothermal (330℃) conditions for 4h;
[0044] (2) drying the material obtained in step (1) at 120° C. for 24 h, and then sintering the material at 560° C. for 30 min using a microwave heating device to obtain zirconium oxide-coated alumina powder;
[0045] (3) The zirconium oxide-coated alumina powder, PVA (average particle size of 1 μm), RO water and appropriate amounts of polysiloxane defoaming agent and methyl cellulose thickener obtained in step (2) are ball-milled for 4 hours using a ball mill, wherein the ratio of the zirconium oxide-coated alumina powder, PVA, RO water, polysiloxane defoaming agent and methyl cellulose thickener is 24wt%: 2.5wt%: 71.5wt%: 0.03%: 1.97wt%.
[0046] (4) coating the material obtained in step (3) on a high temperature resistant gas filtering cordierite support to obtain a wet blank.
[0047] (5) The wet blank obtained in step (4) is dried in the shade at room temperature for 4 hours, then slowly heated to 105°C in an oven and dried for 2 hours, and then subjected to secondary high-temperature sintering in a high-temperature sintering electric kiln at 1350°C for 4 hours to obtain the high-temperature resistant special gas filtration alumina ceramic membrane (the surface morphology is basically the same as that in Example 1).
[0048] The performance of the high temperature resistant special gas filtering alumina ceramic membrane is as follows: temperature resistance up to 350℃, thermal shock resistance (thermal shock resistance test: the filter membrane does not crack or fall off after being rapidly cooled from 350℃ to room temperature for more than 10 times), and its 350℃ thermal shock resistance test can reach 13 times. In comparison, the ceramic membrane made by simple mechanical mixing of the same raw materials has a temperature resistance of only 130℃ (thermal shock resistance test: the filter membrane does not crack or fall off after being rapidly cooled from 130℃ to room temperature for more than 10 times), and its 350℃ thermal shock resistance test is only 0 times.
[0049] According to the above embodiments, the temperature resistance range of the ceramic membrane prepared by the present invention is extended from 10-120°C to 10-350°C, and the thermal shock resistance (the filter membrane does not crack or fall off when rapidly cooled from 350°C to room temperature) is improved from the original 0-1 times to 10-15 times.
[0050] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.
Claims
1. A high temperature resistant special gas filtering alumina ceramic membrane and a preparation method thereof, characterized in that: The steps include: (1) mixing an alumina ceramic powder having an average particle size of 100-800 nm with a nano zirconium oxide dispersion having a concentration of 5-10 wt %, and reacting the mixture under high pressure hydrothermal conditions of 10-16 MPa and 300-350° C. for 3-5 h, wherein the average particle size of the nano zirconium oxide in the nano zirconium oxide dispersion is 10-30 nm; (2) drying the material obtained in step (1), and then sintering it once at 520-580° C. for 25-35 min using a microwave heating device to obtain zirconium oxide-coated alumina powder; (3) ball-milling and mixing the zirconium oxide-coated alumina powder obtained in step (2), PVA with an average particle size of 0.8-1.2 μm, RO water, polysiloxane defoamer and methyl cellulose thickener uniformly; (4) coating the material obtained in step (3) on a high temperature resistant gas filter support to obtain a wet blank; (5) The wet blank obtained in step (4) is shade-dried at room temperature, then dried, and then sintered at 1350-1450° C. for 3-5 hours to obtain the high-temperature resistant special gas filtering alumina ceramic membrane.
2. The preparation method according to claim 1, characterized in that: In the step (1), the purity of Al2O3 in the alumina ceramic powder is greater than 99.9%, and the purity of ZrO2 in the nano zirconium oxide is greater than 99.9%.
3. The preparation method according to claim 1, characterized in that: The drying temperature in step (2) is 120° C. and the drying time is 4 hours.
4. The preparation method according to claim 1, characterized in that: In the step (3), the ratio of zirconium oxide-coated alumina powder, PVA, RO water, polysiloxane defoamer and methyl cellulose thickener is 20-25wt%: 2-2.5wt%: 70-77wt%: 0.01-0.03wt%: 0.99-2.48wt%.
5. The preparation method according to claim 4, characterized in that: In the step (3), the average particle size of the PVA is 1 μm.
6. The preparation method according to claim 1, characterized in that: In the step (4), the shade drying time is 4 hours.
7. The preparation method according to claim 1, characterized in that: In the step (4), the drying temperature is 105° C. and the drying time is 2 hours.
8. The preparation method according to claim 1, characterized in that: In the step (1), the purity of Al2O3 in the alumina ceramic powder is greater than 99.9%, and the purity of ZrO2 in the nano zirconium oxide is greater than 99.9%; in the step (3), the ratio of zirconium oxide-coated alumina powder, PVA, RO water, polysiloxane defoamer and methyl cellulose thickener is 20-25wt%: 2-2.5wt%: 70-77wt%: 0.01-0.03wt%: 0.99-2.48wt%.
9. The preparation method according to claim 8, characterized in that: In the step (3), the average particle size of the PVA is 1 μm.
10. The preparation method according to claim 9, characterized in that: In the step (4), the shade drying time is 4 hours; the drying temperature is 105° C. and the drying time is 2 hours.
